2013
DOI: 10.1111/eci.12090
|View full text |Cite
|
Sign up to set email alerts
|

Financial, nonfinancial and editors' conflicts of interest in high‐impact biomedical journals

Abstract: Purpose To assess financial, nonfinancial and editors' conflicts of interest (COI) disclosure policies among the most influential biomedical journals publishing original research. Materials and methodsWe conducted a cross-sectional study of 399 high-impact biomedical journals in 27 biomedical categories of the Journal Citation Reports (JCR) in December 2011. Information relevant to COI and requirements for disclosures that was publicly available on journal websites was collected.Results While financial COI dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 32 publications
3
41
0
3
Order By: Relevance
“…Non-financial conflicts of interest in medical research and practice, which include those of a political, ideological, individual, or religious nature,12 are often overlooked, denied, and even defined out of existence 34. The focus is directed instead towards financial interests, such as those stemming from drug industry sponsorship of research, or payments to doctors.…”
Section: Yes—miriam Wiersma Ian Kerridge Wendy Lipworthmentioning
confidence: 99%
“…Non-financial conflicts of interest in medical research and practice, which include those of a political, ideological, individual, or religious nature,12 are often overlooked, denied, and even defined out of existence 34. The focus is directed instead towards financial interests, such as those stemming from drug industry sponsorship of research, or payments to doctors.…”
Section: Yes—miriam Wiersma Ian Kerridge Wendy Lipworthmentioning
confidence: 99%
“…4 ) This indicates that there is a great need to ensure that COI disclosure policies are enforced for editors and publishers as well 5 ) as little is known about how COI disclosure of editors and publishers are managed and how effective they are in ensuring transparency in the medical publication process.…”
Section: Year: 2009mentioning
confidence: 99%
“…4) 5) 6) 1) Associate Professor, Department of International Medical Communications, Tokyo Medical University 2) Member, COPE 3) Freelance Translator 4) Emeritus Professor, Tokyo Medical University 5) Council Member, COPE 6) Adjunct Professor, Seoul National Bundang Hospital…”
mentioning
confidence: 99%
“…12 Bosch et al found also in 2011 that among high-impact medical journals, 38.8% required COI disclosure from editors. 13 There is a paucity of studies that examine actual industry payments to medical editors, and these existing studies have been based on voluntary data from editors rather than a broad inclusive database with mandatory reporting. Wong et al surveyed 95 editors-in-chief of clinical medical journals in 2009 and found that 9% reported receiving $1,000 or more from industry in the past year.…”
Section: Introductionmentioning
confidence: 99%